Does Obesity Affect the Outcomes of Primary Total Knee Arthroplasty? - Issa, Kimona; Pivec, Robert; Kapadia, Bhaveen H.; Shah, Tarak; Harwin, Steven F.; Delanois, Ronald E.; Mont, Michael A. (The Journal of Knee Surgery, 2013)
The purpose of this study was to compare the clinical and radiographic outcomes of primary total knee arthroplasty (TKA) in obese and nonobese patients. A total of 210 knees in 174 obese patients who had a mean body mass index (BMI) of 34 kg/m2 (range, 30 to 39.9 kg/m2) and who had undergone a primary TKA between 2006 and 2010 were reviewed. There were 115 women and 59 men who had a mean age of 62 years (range, 36 to 84 years) and a mean follow-up of 57 months (range, 24 to 82 months). These patients were compared with a group of nonobese patients who had a BMI of less than 30 kg/m2 (range, 19 to 29.9 kg/m2). The evaluated outcomes included implant survivorship, Knee Society objective and functional scores, complication rates, radiographic outcomes, University of California Los Angeles (UCLA) activity score, and the length of hospital stay between obese and nonobese patients. There were no significant differences in the overall septic and aseptic implant survivorship (98.8 vs. 98.6%) and mean postoperative Knee Society objective and function scores (90 and 87 points vs. 91 and 89 points), respectively. Obese patients had significantly higher complication rates (10.5 vs. 3.8%) and had achieved a significantly lower mean postoperative UCLA activity score (5 vs. 6 points). However, there were no differences in the length of hospital stay for the two cohorts. Although the authors encourage all patients to lose weight as much as possible prior to their TKA, it is encouraging that obese patients had achieved excellent clinical outcomes at early to mid-term follow-up.
Keywords: total knee arthroplasty; obesity; implant survivorship; Knee Society scores